Efforts to Raise Traditional Market Potential by Developing Market Management Systems and Patterns - Vicki Dwi Purnomo; Kelik Endro Suryono (Indonesian Journal of Society Development, 2023)
Converting market potential into behavior requires a systematic approach. To realize this potential, it is very important to manage the market in accordance with predetermined theories and methods. This study focuses on the potential of the Wates Market to support the local economy. The main objective is to evaluate the impact of market potential management on improving the local community's economy. This study aims to identify the potential to support the local economy in Wates Market and determine its impact on economic growth. The research results show that Wates Market has the potential to support the local economy through lower prices, diverse product offerings, and strategic location. Effective management of market potential has a significant impact on community economic growth, because market managers tend to favor superior products